The evaluation of three comorbidity indices in predicting postoperative complications and readmissions in pediatric urology - Jiang, Ruiyang (J Pediatr Urol, 2018)
INTRODUCTION: The surgical comorbidity assessment is important for patient risk stratification, counseling, and research. In adults, risk assessment indices, such as the Charlson Comorbidity Score (CCS) or Van Walraven Index (VWI), are well established. In pediatrics, however, risk assessment indices are scarce. Recently, a pediatric-specific risk assessment index, the Rhee index, was developed to discriminate mortality for pediatric general surgery patients. Currently, there is no validated risk assessment tool in pediatric urology. OBJECTIVE: We compared the performance of the CCS, VWI, and Rhee Index in discriminating postoperative complications and readmissions to the emergency room/inpatient unit after pediatric urological procedures. METHODS: We analyzed the Nationwide Readmissions Database (NRD), State Inpatient Databases (SID), and State Emergency Department Databases (SEDD). We included patients (< 18 years) who underwent the following urological procedures: ureteroneocystostomy, ureteroureterostomy, radical/partial nephrectomy, pyeloplasty, appendicovesicostomy, enterocystoplasty, vesicostomy, and bladder neck sling. Complications were identified based on definitions in the National Surgical Quality Improvement Program (NSQIP). Thirty-day emergency room admission and inpatient readmissions were extracted. Comorbidity scores were calculated using each of the three indices. We compared the performance of each index in discriminate primarily postoperative complications in the NRD and both admission types in the SID/SEDD by constructing a receiver operating characteristics (ROC). AUCs were compared using the Delong method. This protocol was reviewed by our Institutional Review Board and deemed to be exempt. RESULTS: We identified a total of 8,006 patients in NRD and 6,236 patients in SID/SEDD. The Rhee index had the best performance for discriminating postoperative complications (AUC = 0.67, 95% CI 0.64–0.70) compared to CCS (AUC = 0.62, 95% CI 0.60–0.65) and VWI (AUC = 0.62, 95% CI 0.59–0.65); p < 0.01. The CCS had the best performance for discriminating 30-day inpatient readmissions (AUC = 0.63, 95% CI 0.61–0.66) than VWI (AUC = 0.54, 95% CI 0.52–0.57), and Rhee Index (AUC = 0.56, 95% CI 0.54– 0.59); p < 0.0001. All three indices had similarly poor discrimination for 30-day ER admissions: CCS (AUC = 0.52), VWI (AUC = 0.51), and Rhee Index (AUC = 0.50); p = 0.5. DISCUSSION: The Rhee Index had the best performance for discriminating postoperative complications, while the CCS was superior for discriminating inpatient readmissions among the three indices. Limitations to our study include inpatient-only procedures, inability to identify complications managed in clinics, omission of secondary operations, accounting for parental anxiety, and the generalizability of SID. CONCLUSIONS: The three comorbidity indices evaluated are poor discriminators for postoperative complications, 30-day inpatient readmissions or 30-day ER admissions. A new index is needed for pediatric urology patients.